Strategies for Enhancing Student Motivation and Achievement - Amalia Asy- Syila (Mauve Journal De Leardu, 2024)
In this study, a conceptual literature review is provided to critically analyze some of the ways of increasing student motivation and academic performance in various learning institutions. Knowing the centrality of motivation in influencing learning behavior and learning outcomes, this paper summarizes the current knowledge on Motivation-based effective pedagogical principles such as Self-Determination Theory, Growth Mindset Theory, Goal Orientation and Differentiated Instruction. The strategies identified as key include clear learning objectives, differentiated instructions, development of growth mindsets, group learning environments, and incorporation of technology and gamification to ensure engagement in the process. The results emphasize that the strategies suggested have no blanket effectiveness and must be used with consideration in mind, referring to the specific case and related to the psychological need of humans and students mentioned by Dweck: autonomy, competence, and relatedness. Reflective, evidence-based practice based on the concepts of inclusivity, intrinsic motivation, and holistic development of a student is highlighted in this review. This paper has ended by requesting learning settings which encourage significant interest in and inspiration of inner motives as the channels of long-term academic achievement.